2020
DOI: 10.1016/j.heliyon.2020.e05313
|View full text |Cite
|
Sign up to set email alerts
|

Does professors' gender impact how students evaluate their teaching and the recommendations for the best professor?

Abstract: This study examined the impact of the professors' gender according to a student evaluation of teaching (SET) in a private university. The study took place in a private university (n = 103,833) on six different campuses in the north region of Mexico. The distribution of the professors’ gender was analyzed according to semesters, campuses, and schools. Our findings suggested that when undergraduates evaluated their professors on specific criteria concerning teaching performance, they expressed their opinion rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…With the continued development of higher education [1][2][3][4], determining how to fairly evaluate the teaching quality [5][6][7] of colleges and universities, promote the perfection of teaching objectives, and improve the teaching quality of colleges and universities is the key to furthering educational reform [8,9], and it is also an urgent problem that needs to be solved now. As a result, evaluating teaching quality in colleges and universities has become an important part of the teaching management process [10], and researching methods or models for assessing teaching quality in colleges and universities has become a hot topic for scientific and standardized education and teaching.…”
Section: Introductionmentioning
confidence: 99%
“…With the continued development of higher education [1][2][3][4], determining how to fairly evaluate the teaching quality [5][6][7] of colleges and universities, promote the perfection of teaching objectives, and improve the teaching quality of colleges and universities is the key to furthering educational reform [8,9], and it is also an urgent problem that needs to be solved now. As a result, evaluating teaching quality in colleges and universities has become an important part of the teaching management process [10], and researching methods or models for assessing teaching quality in colleges and universities has become a hot topic for scientific and standardized education and teaching.…”
Section: Introductionmentioning
confidence: 99%
“…There are some mixed results; for instance, when shifting from in-person to online teaching, the SET scores lowered for faculty in communication courses (LeBlanc, 2021). Regarding gender bias, several studies have found no significant gender-related differences in students' evaluation of teaching in different contexts (Arrona-Palacios et al, 2020;Tangalakis et al, 2022). However, in the COVID-19 pandemic, male students make more negative comments about their female professors' teaching style (Tangalakis et al, 2022).…”
Section: Student Evaluation Of Teachingmentioning
confidence: 99%
“…There is a solid body of data about the semesters prior to AD2019, and with respect to the traditional educational model hence minimal premise for comparison between models. The data obtained with students from the traditional educational model has been analyzed and presented in previous studies (Arrona-Palacios et al, 2020;Okoye et al, 2020).…”
Section: Institutional Response To the Covid-19 Pandemic Pre-covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…In [15], the author did a study titled: Does professors' gender effect how students perceive their teaching and suggestions for the best professor? The study revealed that when undergraduates rated their professors on certain criteria related to teaching performance, they shared their opinions independently of the professors' gender.…”
Section: Literature Reviewmentioning
confidence: 99%